Trust-Based Service Delivery dalam MBKM: Refleksi Pengalaman Mahasiswa Administrasi Pendidikan Universitas Jambi : Penelitian - Handoko, Yudo; Soleh, Warissuddin; Musyaiyadah, Musyaiyadah; Ramadhoni, Sri Rahmah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to understand the relationship between the quality of academic and administrative services and student trust in the implementation of the Independent Learning Campus (MBKM) program in the Educational Administration Study Program at the University of Jambi. The flexibility of MBKM presents new challenges in the governance of higher education services, particularly in the aspects of communication, academic mentoring, and administration. Therefore, it is important to examine student perceptions and their influence on participation and learning experiences. The study used a qualitative approach with an intrinsic case study. Data were collected through in-depth interviews, participant observation, and institutional document review. Then, they were validated through triangulation and analyzed using the interactive model of Miles, Huberman, and Saldana. The results showed positive student perceptions of academic services, especially communicative and responsive lecturer mentoring, while administrative services were still hampered by bureaucracy and document delays. Student trust is formed through transparency, commitment, consistency, and institutional concern, which synergistically with service quality directly influence student participation and active involvement in MBKM. The study concluded that the success of MBKM is determined by the quality of institutional services and student trust, making trust-based services key to the effectiveness of its implementation in higher education.